The Role Of The Legislature, In Maintaining The Balance Of Power In The Constitutional Legal System - Akili, Rustam HS (Jurnal Multidisiplin Sahombu, 2023)
One of the most important parts of the constitutional legal system is that each state entity has an equal amount of power. In a democratic government, this balance of power is kept in large part by the legislature. But many things can affect how well the legislature does its job and how it keeps the balance of power in the constitutional law system. The goal of this study is to look at how the government keeps the balance of power in a constitutional legal system. This study uses a normative legal method to look at the role of the legislature in making sure that other state institutions have the same amount of power. The study's results show that the legislature's job is to keep the balance of power in the constitutional legal system. This is done by making laws, keeping an eye on things, asking questions, and giving views. But there are things that make it hard for the legislature to do its job, like the system and process of checks and balances in the Constitution as it was changed in 1945. In theory, having the Constitution of 1945 is no longer enough to make it a constitutional document that can bridge and protect all of the state's democratic processes. So, work needs to be done to improve the legislature's institutional role in keeping the balance of power in the constitutional judicial system.